2017
DOI: 10.5604/01.3001.0009.8411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for oral cavity and oropharynx cancer in the authors’ own material

Abstract: The major part of the examined patients were women and men with the secondary and high level of education, 47,76% and 35,82%, and 58,97% and 35,91% respectively. The patients were informed by mass media about the planned preventive medical examinations - 80,60% women and 79,49% men. The most common symptoms reported by women were: hoarse voice in 61,19% cases, dysphagia in 32,84% cases and burning sensation and/or pain in the oral cavity in 29,85% cases. The examined male patients mainly showed hoarse voice (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…Independent from smoking and alcohol, family history among first-degree relatives is a strong determinant of oral and pharyngeal cancer risk. [16] Our study group revealed that 33.5% of all subjects had cancer diagnosis of any type of first-degree relatives, which also increases the risk of recalling the disease. The elevated risks in genetic predisposancy in familial cancers may also be due to shared environmental exposure.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Independent from smoking and alcohol, family history among first-degree relatives is a strong determinant of oral and pharyngeal cancer risk. [16] Our study group revealed that 33.5% of all subjects had cancer diagnosis of any type of first-degree relatives, which also increases the risk of recalling the disease. The elevated risks in genetic predisposancy in familial cancers may also be due to shared environmental exposure.…”
Section: Discussionmentioning
confidence: 77%
“…The main causes in aetiology are tobacco and alcohol usage in 90% of the cases, as well as genetic background, personal exposures and oncogenic virus contamination have a considerable impact. [2][3][4] By reducing tobacco and alcohol usage mostly in public common places and providing cessation support, public health initiatives are contributing to the prevention of the malignancies. [5][6] Common symptoms of oral cancers may include red/white lesions that are regarded as potentially malignant disorders, oral ulcers/pharyngitis, swelling of the mouth/neck, numbness of the perioral area and bloody postnasal drainage for a prolonged time period.…”
Section: Introductionmentioning
confidence: 99%
“…The dental students could be influenced by their peers' beliefs and behavior towards performing oral cancer examinations or educating patients about oral cancer risk factors. Moreover, the perceived school support for the practice, and the degree of dental students' motivation to comply with their fellow students' and supervisors' beliefs and behavior may influence dental students, as well [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, slightly more than half of the participants expressed positive feelings (would feel comfortable) about being examined for oral cancer (item 34). The majority of participants had favorable attitudes toward different oral cancer preventative measures, such as health education, community lectures and symposiums, and distributions of written educational material about oral cancer (items 36,37,38,39). Around three-quarters of the participants were in favor of banning Ghat, Shamma and tobacco as a way of preventing oral cancer in the community (item 40; table 3.3.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation